Designing, implementing and evaluating the overdose response with take‐home naloxone model of care: An evaluation of client outcomes and perspectives. (27th November 2019) - Lintzeris, Nicholas; Monds, Lauren A.; Bravo, Maria; Read, Phillip; Harrod, Mary E.; Gilliver, Rosie; Wood, William; Nielsen, Suzanne; Dietze, Paul M.; Lenton, Simon; Shanahan, Marian; Jauncey, Marianne; et al.
Abstract: Introduction and Designs: Take‐home naloxone (THN) interventions are an effective response to preventing overdose deaths, however uptake across Australia remains limited. This project designed, implemented and evaluated a model of care targeting opioid users attending alcohol and other drug (AOD) treatment, needle and syringe programs (NSP) and related health services targeting people who inject drugs. Design and Methods: Service providers, consumers and regulators collaboratively designed a THN brief intervention (ORTHN, Overdose Response with Take‐Home Naloxone) involving client education and supply of naloxone in pre‐filled syringes, delivered by nursing, allied health and NSP workers. ORTHN interventions were implemented in over 15 services across New South Wales, Australia. The evaluation included client knowledge, attitudes, substance use and overdose experiences immediately before and 3 months after ORTHN intervention in a subsample of participants. Results: Six hundred and sixteen interventions were delivered, with 145 participants recruited to the research subsample, of whom 95 completed the three‐month follow up. Overdose‐related attitudes amongst participants improved following ORTHN, with no evidence of increased substance use or failure to implement other 'first responses' (e.g. calling an ambulance). Nine participants (10%) reversed an overdose using THN in the follow‐up period. Participants identified a willingness to access THN from a range of services. While a minority (16%) indicated they were unwilling to pay for THN, the median price that participants were willing to pay was AUD20 (IQR 10.40). Discussion and Conclusions: The ORTHN model of care for THN appears an effective way to disseminate THN to people who use opioids attending AOD, NSP and related health‐care settings.